Infectious diarrhea: Pathogenesis and risk factors - Cantey, J.Robert (Am J Med, 1985)
Our understanding of the pathogenesis of infectious, especially bacterial, diarrhea has increased dramatically. New etiologic agents, mechanisms, and diseases have become known. For example, Escherichia coli serogroup 0157 is now known to cause acute hemorrhagic colitis. Also, E. coli serogroups that produce Shiga toxin are recognized as etiologic agents in the hemolytic-uremic syndrome. The production of bacterial diarrhea has two major facets, bacterial-mucosal interaction and the induction of intestinal fluid loss by enterotoxins. Bacterial-mucosal interaction can be described in stages: (1) adherence to epithelial cell microvilli, which is often promoted by or associated with pill; (2) close adherence (enteroadherence), usually by classic enteropathogenic E. coli, to mucosal epithelial cells lacking microvilli; and (3) mucosal invasion, as with Shigella and Salmonella infections. Further large strides in understanding infectious diarrhea are likely with the cloning of virulence genes if additional host-specific animal pathogens become available for study.